Marxism and the agrarin question - Hussain, Athar (London, 1983)
Written as a single text in 1978-79, this book was split into two volumes according to the principal subject-matter and issued as a hardback in 1981. For this one-volume paperback edition we have restored the original form and taken the opportunity of correcting some errors, but have left the text itself unaltered. While we both might wish to change certain emphases in the concluding chapter, neither felt that these were of a significance to demand a redrafting. Naturally enough if the book were to be written now it might turn out very different; the arguments advanced in the body of the book, however, are we believe valid and defensible, and we do not wish to alter them
Keywords: Socialism